Discovery of Quality Markers in Hugan Qingzhi Formula by Integrating a Lipid-Lowering Bioassay with UHPLC-QQQ-MS/MS. (12th November 2020) - He, Fan; Xiao, Chun-Xin; Wang, Can-Jian; Liang, Jie; Cheng, Qi-Qing; Zhang, Li; Zhou, Ben-Jie; Zhou, Hua
Abstract : Nonalcoholic fatty liver disease (NAFLD) is a prevalent chronic liver disease. The Hugan Qingzhi formula (HGQZ) has been proven effective in treating NAFLD through clinical and pharmacological mechanism studies. A screening study of the chemical components was carried out to better control the quality of this formula. Current research has combined biological activity assessment with chemical analysis to screen and identify the bioactive compounds in HGQZ for use as potential quality markers (Q-markers) to control the quality of this herbal product. The HGQZ extracted by three different solvents was evaluated in a free fatty acid-induced hepatic steatosis LO2 cell model. Simultaneously, the twelve major chemical constituents of these extracts were quantitatively measured by ultrahigh-performance liquid chromatography coupled with triple quadrupole mass spectrometry (UHPLC-QQQ-MS/MS). Extraction with 50% ethanol showed the most potent lipid-lowering effect in steatosis LO2 cells and the highest extraction rate of major chemical constituents. Correlation analysis was used to establish the relationship between the biological activities and chemical characteristics of these extracts. The results showed that the contents of typhaneoside, hyperoside, isoquercitrin, isorhamnetin-3-O-neohesperidoside, notoginsenoside R1, and alisol B 23-acetate were positively correlated to the lipid-lowering effect. The subsequent bioassay confirmed that typhaneoside, isoquercitrin, and alisol B 23-acetate played the role of reducing the lipid effect. In conclusion, 50% of ethanol extraction produced the most active extract of HGQZ. Typhaneoside, isoquercitrin, and alisol B 23-acetate could be considered potential Q-markers for the quality control of HGQZ.